Innovations in Gearing the Housing Market to Welfare Recipients in Osaka's Inner City: A Resilient Strategy?. Issue 4 (2nd October 2018) - Kiener, Johannes; Kornatowski, Geerhardt; Mizuuchi, Toshio
ABSTRACT: For this paper we apply the framework of resilience as an adaptive process to examine alternative practices that assist socially vulnerable populations into the urban fabrik. The recent direction of Osaka's inner city rental housing market for public assistance recipients is used as case study. We look on systemic aspects such as changing tenant revenues and welfare policies, and analyze the innovative housing reuse practices of local landlords and real estate agents. Our results show that the resilience-producing systemic properties are co-produced by public assitance policies, the particular condition of Osaka's inner city and individual stakeholders' actions. While these stakeholders have benefited immensely from the housing market's resilient response, it is structured by uneven dependencies, which ultimately affects the housing opportunities and care services for current and future tenants.